Performance Analysis of Probabilistic Relay UAV Selection Method Considering Neighbor UAV Characteristics in FANETs - Kim, Youbin; Lee, Yerin; Jeon, Jimin; Choi, Jungwook; Park, Soobum; Jung, Bang Chul; Lee, Howon (Journal of Korean Institute of Communications and Information Sciences, 2024)
In FANETs (flying ad hoc networks), efficient and effective relay selection is crucial to increase coverage probability while reducing unnecessary packet transmissions. This paper proposes a probabilistic relay node selection method considering uncovered neighbors to minimize network performance degradation caused by coverage overaps and redundant packet transmissions. Through various simulations, it is shown that the proposed method outperforms benchmark methods in terms of total number of packet transmission, coverage probability, and energy efficiency.
Keywords: aerial relay selection; FANET; probabilistic relay; UAV; uncovered neighbor